Vitamin C : new biochemical and functional insights - Chen, Qi; Vissers, Margreet C. M. (Margreet Catherina Maria) (Boca Raton : CRC Press, 2020)
Vitamin C holds a unique place in scientific and cultural history. In this book, a group of leading scientific research explore the myriad ways Vitamin C is employed during normal physiological function. This book also provides updates on recent uses ofVitamin C in cancer treatment through high dose intravenous therapies, the ways Vitamin C reduces or prevents sepsis and in the treatment of infectious disease, and the ways Vitamin C improves succesful stem cell transplantation, as well as other health implications. Key selling features: Reviews the history and recent research on the benefits and uses of Vitamin C Focuses special attention on the ways Vitamin C can be used in the treatment of cancers Discusses how Vitamin C is employed against infectious disease Includes chapters from a team of leading international scholars
Introduction: on intensive physiology study leads to implications in diseases. Part I Chemistry and physiology of vitamin C. Discovery of vitamin C: the history. Basics of vitamin C: chemistry, and redox biochemistry. Vitamin C physiology: transporters and metabolism. Vitamin C biological functions as co-factors for enzymes, such as in biosynthesis of collagen, carnitine, neurotransmitters, and others. Part II vitamin C and cancer. History in cancer treatment: Linus Pauling's theory and the conflict with Mayo Clinic trials. High dose intravenous ascorbate (IVC): prooxidant actions. IVC as multi-target anti-cancer agent. IVC and epigenetics. IVC in hypoxia. Overview of recent clinical trials. IVC with radiation therapy. IVC and QOL in cancer patients. with other naturopathy for cancer. Part III Vitamin C and infectious diseases. Vitamin C in sepsis. Vitamin C in other infections. Part IV Vitamin C and stem cells. Vitamin C and bone marrow transplantation. Vitamin C and Tet (s). Vitamin C and somatic cell reprogramming. Part V Vitamin C in other health implications. Vitamin C in the brain/neurotransmitters. Vitamin C in diabetes.
OCLC-licensed vendor bibliographic record.
Keywords: MEDICAL / Pharmacology; SCIENCE / Life Sciences / Biology / Molecular Biology; SCIENCE / Life Sciences / General; Vitamin C -- Therapeutic use; Cancer -- Treatment; Biochemistry